2022
DOI: 10.1080/07853890.2022.2081871
|View full text |Cite
|
Sign up to set email alerts
|

Lower systemic inflammation is associated with gut firmicutes dominance and reduced liver injury in a novel ambulatory model of parenteral nutrition

Abstract: Background Total Parenteral Nutrition (TPN) provides lifesaving nutritional support to patients unable to maintain regular enteral nutrition (EN). Unfortunately, cholestasis is a significant side effect affecting 20–40% of paediatric patients. While the aetiology of TPN-associated injury remains ill-defined, an altered enterohepatic circulation in the absence of gut luminal nutrient content during TPN results in major gut microbial clonal shifts, resulting in metabolic endotoxemia and systemic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This variation is likely attributable to the antimicrobial properties of probiotics in the fermented feed. Firmicutes, a phylum of critical bacterial, play a vital role in the production of short-chain fatty acids (SCFAs), providing an efficient energy source for intestinal cells and augmenting carbohydrate absorption in the host [34]. In this study, the Firmicutes to Bacteroidetes ratio (F:B) was dose-dependently reduced by the inclusion of fermented feed.…”
Section: Discussionmentioning
confidence: 89%
“…This variation is likely attributable to the antimicrobial properties of probiotics in the fermented feed. Firmicutes, a phylum of critical bacterial, play a vital role in the production of short-chain fatty acids (SCFAs), providing an efficient energy source for intestinal cells and augmenting carbohydrate absorption in the host [34]. In this study, the Firmicutes to Bacteroidetes ratio (F:B) was dose-dependently reduced by the inclusion of fermented feed.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, several diseases are associated with gut microbiota disorders, including NH ( 5). An increasing number of studies have indicated that the gut microbiota regulates bilirubin metabolism through enterohepatic circulation (12)(13)(14). Early evidence from sterile animals suggests that the gut microbiota is necessary for bilirubin metabolism in the intestine (15).…”
Section: Discussionmentioning
confidence: 99%
“…Our results reported similar to those of Wang C. et al (2021) . Furthermore, studies have indicated that increasing firmicutes might reduce the body’s inflammatory response ( Samaddar et al, 2022 ). BA treatment enhanced the relative abundance of Lactobacilli while decreasing the relative abundance of Shivering spiralis at the genus level.…”
Section: Discussionmentioning
confidence: 99%